Sinapic acid alleviates inflammatory bowel disease (IBD) through localization of tight junction proteins by direct binding to TAK1 and improves intestinal microbiota - Jang, Sehyeon; Kim, San; So, Bo Ram; Kim, Younghoon; Kim, Chang-Kil; Lee, Jeong Jae; Jung, Sung Keun (Frontiers in Pharmacology, 2023)
Although sinapic acid is found in various edible plants and has anti-inflammatory properties, particularly in colitis, its underlying mechanism and effects on the composition of the gut microbiota are largely unknown. We aimed to identify an early-response kinase that regulates the localization of tight junction proteins, acts at the onset of the inflammatory response, and is regulated by sinapic acid. Additionally, we analyzed the effects of sinapic acid on the homeostasis of the intestinal microbiome. We confirmed that sinapic acid significantly suppressed the stimulus-induced delocalization of tight junction proteins from the intestinal cell membrane and abnormal intestinal permeability as well as the expression of inflammatory cytokines, including interleukin-1β and tumor necrosis factor-α in vitro and in vivo. Sinapic acid directly bound to transforming growth factor beta-activated kinase 1 (TAK1) and inhibited the stimulus-induced activation of nuclear factor-kappa B (NF-κB) as well as mitogen-activated protein kinase/activating transcription factor-2 (MAPK/ATF-2) pathways, which in turn regulated the expression of myosin light chain kinase (MLCK). Furthermore, dietary sinapic acid alleviated the imbalance of gut microbiota and symptoms of inflammatory bowel disease (IBD), as evidenced by improvements in the length and morphology of the intestine in mice with colitis. Interestingly, oral administration of sinapic acid significantly prevented DSS-induced decrease in Shannon diversity. Additionally, sinapic acid inhibited DSS-induced declines in the relative abundance of Ligilactobacillus and Limosilactobacillus at the genus level in feces of C57BL/6J mice. These findings indicate that sinapic acid may be an effective nutraceutical and pharmaceutical agent for IBD treatment as it targets TAK1 and inhibits subsequent NF-κB and ATF-2 signaling and gut microbiome dysbiosis.